UHPC based on graphene oxide modification and preparation method and application thereof

By adding oxygen oxygenne to ultra -high -performance concrete, it promotes hydrophilic reactions and forms a dense micro -structure, solving the problem of ultra -high -performance concrete anti -invasion performance platform effects, and achieves the effect of significantly improved anti -invasion and mechanical properties.

CN119371167AInactive Publication Date: 2025-01-28SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411986324.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Ultra-high performance concrete has a platform effect in terms of intrusion resistance. The aggregate-matrix interface transition zone limits the further improvement of intrusion resistance, and the impact of existing components on intrusion resistance is different, making it difficult to effectively improve.

Method used

By adding oxygen oxygenne in ultra -high -performance concrete, using its oxygen -containing functional group and calcium ions in the cement to promote the production and hydration response of calcium silicate gel, to form a more dense micro structure and hydrophilization Product network.

Benefits of technology

显著提高了超高性能混凝土的抗高速弹体侵彻性能和力学性能,增强了材料的韧性和抗冲击能力,减少了侵彻深度和开坑直径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371167A_ABST
    Figure CN119371167A_ABST
Patent Text Reader

Abstract

The invention discloses UHPC based on graphene oxide modification and a preparation method and application thereof, and belongs to the technical field of novel building materials. The high-performance concrete is prepared from the following raw materials in parts by mass: 1417 to 1517 parts of cement, 135 to 165 parts of silica fume, 35 to 43 parts of steel fiber, 0.29 to 0.73 part of graphene oxide, 410 to 510 parts of water and 6 to 12 parts of polycarboxylic acid type high-efficiency water reducing agent. The graphene oxide comprises oxygen-containing functional groups, and the oxygen-containing functional groups are complexed with calcium ions in cement by utilizing the hydrophilicity of the oxygen-containing functional groups, so that the generation of strong covalent bond hydrated calcium silicate gel is promoted, and a more compact microstructure and a more compact hydration product network are formed around the graphene oxide. And nucleation sites are provided for growth of hydrated crystals, growth of needle-shaped and rod-shaped crystals is promoted along with graphene oxide, regular and compact microstructures can be formed with columnar and flower-shaped hydrated crystals, and the anti-penetration performance of the cement-based composite material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of novel building materials, and in particular relates to a UHPC modified by graphene oxide, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material with ultra-high strength, high toughness and high durability. Compared with ordinary concrete, ultra-high performance concrete has significant advantages in terms of penetration and explosion resistance. For example, under the same penetration conditions, its penetration depth and pit damage are much smaller than ordinary concrete. However, after the strength of ultra-high performance concrete is increased to a certain threshold, its higher compressive strength cannot be effectively converted into penetration resistance, that is, there is a platform effect.

[0004] The anti-penetration bottleneck of ultra-high performance concrete can be attributed to the following aspects. Although aggregates improve the anti-penetration performance of ultra-high performance concrete to a certain extent, the addition of aggregates also introduces a relatively weak aggregate-matrix interface transition zone, which limits the further improvement of anti-penetration performance. In the past, concrete focused on its compressive strength, so the common components of concrete were mostly used to improve compressive strength and static mechanical properties. However, when these common components are applied to ultra-high performance concrete, they need to be re-evaluated and screened because of their different micromorphologies and chemical properties, which will have different effects on the anti-penetration performance. The main hydration product of the ultra-high performance concrete matrix is ​​calcium silicate hydrate gel (CSH). About 1 / 3 of the calcium silicate hydrate gel is connected by weak van der Waals force, which can be invalidated with very low energy. In addition, the material expands or contracts during the formation of CSH gel. This volume change will produce stress concentration when restricted by other components of the matrix, leading to the formation of microcracks, thereby limiting the anti-penetration ability of the ultra-high performance concrete matrix. In recent years, high-strength and high-hardness coarse aggregates (such as sintered bauxite coarse aggregates) have been successfully introduced into ultra-high performance concrete to improve its anti-penetration performance, especially the penetration depth. However, due to the limitations of van der Waals forces and micro-cracks in the pores of the material, the anti-penetration ability of the ultra-high performance concrete matrix is ​​still difficult to effectively improve, which limits the promotion and application of ultra-high performance concrete in protective engineering. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a UHPC based on graphene oxide modification and a preparation method and application thereof, and to modify the ultra-high performance concrete matrix using graphene oxide to improve its anti-penetration performance under the action of high-speed projectiles.

[0006] In order to achieve the above object, the technical solution of the present invention is: In a first aspect, the present invention provides a UHPC based on graphene oxide modification, which is prepared from raw materials including the following components in parts by weight: 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 0.29-0.73 parts of graphene oxide, 410-510 parts of water and 6-12 parts of water reducing agent; Among them, the molecular structure formula of graphene oxide is: .

[0007] Components that undergo a high-temperature melting process during the production process, such as slag powder, steel slag, etc., are not added. Because these components have a relatively smooth microstructure after undergoing a high-temperature melting process. Although this structure has a positive effect on the compressive performance, it will cause a loose bond between it and the matrix in situations where the anti-penetration performance needs to be improved. It can only play the role of filling the hydration product network and cannot form a dense rigid whole with the hydration product network. In addition, due to the smooth microstructure, its specific surface area is small, resulting in a small number of effective connection structures (such as hydrogen bonds or various chemical bonds) generated on the surface, which cannot have a favorable effect on the anti-penetration performance. Therefore, when it is necessary to improve the anti-penetration performance, it is necessary to avoid the addition of slag powder, steel slag and other components as much as possible according to the performance requirements.

[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned UHPC based on graphene oxide modification, comprising the following steps: S1, mixing graphene oxide and water to obtain a graphene oxide dispersion; S2, cement and silica fume are mixed to obtain a first mixture; S3, adding the graphene oxide dispersion to the first mixture, and mixing to obtain a second mixture; S4. Add steel fiber to the second mixture, mix and stir to obtain the graphene oxide-modified UHPC.

[0009] In a third aspect, the present invention provides the application of the above-mentioned graphene oxide modified UHPC in protective engineering.

[0010] The beneficial effects of the present invention are: The graphene oxide added in the present invention includes oxygen-containing functional groups (such as carboxyl, hydroxyl and epoxy groups), which utilize their hydrophilicity to complex with calcium ions in cement to promote the formation of strong covalent bond hydrated calcium silicate (CSH) gel. This can replace the weak van der Waals force in the original CSH, catalyze and promote the hydration reaction in cement, and form a denser microstructure and a denser hydration product network around the graphene oxide. At the same time, the oxygen-containing functional groups provide active sites for the hydration products, which can promote the nucleation and crystal growth of calcium hydroxide in the hydration products, thereby improving the early strength and hydration rate of the cement matrix. On the other hand, the addition of graphene oxide regulates the hydration products of cement. During the hydration reaction, the oxygen-containing functional groups on graphene oxide (including -OH, -COOH, -CH(O)CH and -SO3, etc.) react with the active ingredients in cement (C3A, C3S, C2S, C4AF), providing nucleation sites for the growth of hydrated crystals. As graphene oxide promotes the growth of needle-shaped and rod-shaped crystals, it can form a regular and dense microstructure with columnar and flower-shaped hydrated crystals, further improving the anti-penetration performance of cement-based composites. In addition, flower-shaped polyhedrons and columnar crystals have self-repairing effects, which can repair the holes and gaps formed in the early stages of pouring and curing of cement-based materials, and have good reinforcement and toughening effects. In addition, the addition of graphene oxide inhibits the generation of corrosive compounds (calcium sulfate), and the multiple effects work together to greatly improve the anti-penetration ultra-high performance concrete based on graphene oxide modification. Avoid adding ingredients that undergo high-temperature melting processes, such as steel slag, slag powder, etc., to other components to strengthen the mechanical interlocking effect in the hydration product network, so that the internal structure of the ultra-high performance concrete formed is more conducive to improving the anti-penetration performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0012] Figure 1 It is a schematic diagram of the reaction principle in a specific embodiment of the present invention.

[0013] Figure 2 It is a schematic diagram of the preparation process of graphene oxide in a specific embodiment of the present invention.

[0014] Figure 3 It is a relationship diagram between the graphene oxide dosage in the examples and comparative examples in the specific implementation manner of the present invention and the compressive strength and flexural strength.

[0015] Figure 4 1 is a graph showing the relationship between the graphene oxide dosage in the examples and comparative examples in the specific implementation manner of the present invention and the penetration depth and the pit diameter. DETAILED DESCRIPTION

[0016] A typical embodiment of the present invention provides a UHPC based on graphene oxide modification, which is prepared from raw materials including the following components in parts by weight: 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 0.44-0.58 parts of graphene oxide, 410-510 parts of water and 6-12 parts of water reducing agent.

[0017] Optionally, the cement is ordinary Portland cement of grade 52.5 or grade 52.5R, which has good compatibility with polycarboxylic acid-based high-efficiency water reducing agent.

[0018] Optionally, the silica ash has an amorphous silicon dioxide content greater than 95wt% and a specific surface area greater than 21.0 m 2 / g, with a specific density greater than 2.2, which is an ultra-fine dry powder that has not been fully encrypted.

[0019] Optionally, the steel fiber is ordinary Mercedes-Benz steel fiber or copper-plated straight steel fiber; the average length of the steel fiber is 13 mm, the average diameter is 0.16 mm, the tensile strength is greater than 2500 MPa, the elastic modulus is 200 GPa, and the density is 7800 kg / m 3 .

[0020] Optionally, the typical molecular structure of the graphene oxide is: .

[0021] Optionally, the graphene oxide is prepared by oxidation, filtration and exfoliation processes.

[0022] Optionally, the method for preparing graphene oxide comprises the steps of: S11, adding graphite powder and NaNO3 powder in a mass ratio of 1: (0.5-2) into a set volume of concentrated sulfuric acid, stirring in an ice bath, to obtain a first mixed solution; S12, adding 2 to 3 times the mass of the graphite powder of potassium permanganate to the above concentrated sulfuric acid, mixing and stirring, reacting for 2 to 3 hours, to obtain a second mixed solution; S13, adding water in an amount 1 to 2 times the volume of concentrated sulfuric acid to the second mixed solution under ice bath conditions and heating the mixture to 90 to 97° C., then adding water in an amount 2 to 4 times the volume of concentrated sulfuric acid and H2O2 in an amount 1 / 12 to 1 / 6 of the volume of concentrated sulfuric acid to terminate the reaction, thereby obtaining a dispersion of graphene oxide; S14, filtering the graphene oxide dispersion, washing it, and removing the exfoliation under ultrasonic treatment; S15, freeze-drying the graphene oxide dispersion to obtain graphene oxide for later use.

[0023] A typical embodiment of the present invention provides a method for preparing the above-mentioned UHPC based on graphene oxide modification, comprising: S1, mixing graphene oxide and water to obtain a graphene oxide dispersion; S2, cement and silica fume are mixed to obtain a first mixture; S3, adding the graphene oxide dispersion to the first mixture, and mixing to obtain a second mixture; S4. Add steel fiber to the second mixture, mix and stir to obtain the graphene oxide-modified UHPC.

[0024] Optionally, in S1, the mixing method is ultrasonic stirring for 1 to 2 hours.

[0025] Optionally, in S2, the mixing method is stirring at a rotation speed of 75-85 rpm for 2-3 min.

[0026] Optionally, in S3, the mixing method is stirring at a rotation speed of 75-85 rpm for 2-3 min.

[0027] Optionally, in S3, a water reducing agent is added.

[0028] Optionally, in S4, after the freshly mixed concrete (ie, the second mixture) has good fluidity, the steel fibers are slowly added through a square hole sieve.

[0029] Optionally, in S4, the mixing and stirring method is stirring at a rotation speed of 155-165 rpm for 3-5 min.

[0030] Optionally, the method further includes step S5, mixing the graphene oxide-modified UHPC, casting it into a mold, and curing it to a specified age.

[0031] Optionally, in S5, the stirring method is stirring at a rotation speed of 355-365 rpm for 3-5 min.

[0032] Optionally, in S5, the curing method is to perform curing under standard curing conditions (temperature: 20±2°C, relative humidity: >95%RH).

[0033] A typical embodiment of the present invention provides the application of the above-mentioned UHPC modified by graphene oxide, including application in military protection engineering or civil structural engineering.

[0034] Specifically including: application in fortifications, missile launch sites, nuclear waste storage facilities, war-ready roads or main structures of large-span bridges.

[0035] Preparation Example 1 Methods for preparing graphene oxide, such as Figure 2 As shown, including: S1: Take 2g of graphite powder and 2g of NaNO3 and add them into 96ml of 98% concentrated sulfuric acid. Place it in an ice bath (<5℃) and stir in a three-necked round-bottom flask. S2: 4 g of KMnO4 was added to the container three times under continuous stirring, with an interval of 15 minutes between each addition; the obtained mixture was reacted within two hours and cooled to room temperature, during which oxygen-containing functional groups were inserted into graphene by adding KMnO4 to prepare hydrophilic oxide; S3: After taking out the ice bath liquid, add 80 ml of deionized water and raise the temperature to 90°C, then add 200 ml of deionized water and 10 ml of H2O2 to terminate the reaction; S4: the solution is purified by vacuum filtration and then repeatedly washed with deionized water until the pH value of the solution is close to 7, and the obtained graphene oxide is treated with 35W ultrasound for 4h to remove keratin; S5: finally, the graphene oxide is placed in a freeze dryer and dried for 36 hours to complete the preparation of the graphene oxide; During the whole process, the solution color turns green after oxidation, and changes from brown to bright yellow after filtration.

[0036] Example 1 A UHPC based on graphene oxide modification is prepared from raw materials including the following components in parts by mass: 1467 parts of 52.5-grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 0.29 parts of graphene oxide, 39 parts of copper-plated straight steel fibers, 452 parts of tap water, and 6 parts of a polycarboxylic acid-based high-efficiency water reducer.

[0037] The preparation method comprises: S1. Mix graphene oxide and all water, and stir them by ultrasonic for 1 hour to obtain a graphene oxide dispersion.

[0038] S2, cement and silica fume are mixed and stirred at a speed of 80 rpm (low-speed stirring) for 3 minutes to obtain a first mixture. The low-speed stirring can prevent powder from splashing.

[0039] S3. Add the graphene oxide dispersion and the water reducing agent to the first mixture, stir at a speed of 80 rpm (low speed stirring) for 3 minutes, and mix to obtain a second mixture.

[0040] S4. When the cementitious material of the second mixture can be well mixed and no obvious unhydrated material emerges on the surface of the fresh concrete, indicating that it has good fluidity, slowly add steel fiber through a square hole sieve and stir at a speed of 160 rpm (medium speed stirring) for 5 minutes to obtain UHPC slurry modified by graphene oxide.

[0041] S5. After stirring the graphene oxide-modified UHPC slurry at a speed of 360 rpm (high-speed stirring) for 3 minutes, the slurry was cast and cured to the specified age. The curing conditions were: temperature of 20±2°C and relative humidity of >95%RH.

[0042] Specifically, during the pouring process, use a vibrating table to vibrate lightly for 2 minutes, which helps to expel bubbles and improve its density; after pouring, cover it with plastic film to prevent surface moisture loss, and demold after 24 hours.

[0043] Example 2 A graphene oxide-modified UHPC is prepared from raw materials comprising the following components in parts by mass: 1467 parts of 52.5-grade or 52.5R-grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 0.44 parts of graphene oxide, 39 parts of copper-plated straight steel fibers, 452 parts of tap water, and 8.5 parts of a polycarboxylic acid-based high-efficiency water reducer.

[0044] The raw material requirements and preparation method are the same as those in Example 1.

[0045] Example 3 A graphene oxide-modified UHPC is prepared from raw materials comprising the following components in parts by mass: 1467 parts of 52.5-grade or 52.5R-grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 0.59 parts of graphene oxide, 39 parts of copper-plated straight steel fibers, 452 parts of tap water, and 11 parts of a polycarboxylic acid-based high-efficiency water reducer.

[0046] The raw material requirements and preparation method are the same as those in Example 1.

[0047] Example 4 A graphene oxide-modified UHPC is prepared from raw materials comprising the following components in parts by mass: 1467 parts of 52.5-grade or 52.5R-grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 0.73 parts of graphene oxide, 39 parts of copper-plated straight steel fibers, 452 parts of tap water, and 12 parts of a polycarboxylic acid-based high-efficiency water reducer.

[0048] The raw material requirements and preparation method are the same as those in Example 1.

[0049] Comparative Example 1 A UHPC is prepared from raw materials including the following components by weight: 1467 parts of 52.5 or 52.5R ordinary Portland cement, 147 parts of incompletely densified silica fume, 39 parts of copper-coated straight steel fibers, 452 parts of tap water, and 4 parts of polycarboxylic acid-based high-efficiency water reducer. The difference from Example 1 is that graphene oxide is not added, and other raw material requirements are the same as those of Example 1.

[0050] The preparation method is the same as that of Example 1, except that no graphene oxide is added.

[0051] Comparative Example 2 A graphene oxide-modified UHPC is prepared from raw materials including the following components in parts by mass: 1467 parts of 52.5-grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 85 parts of slag powder, 0.44 parts of graphene oxide, 39 parts of copper-plated straight steel fibers, 452 parts of tap water, and 6 parts of a polycarboxylic acid-based high-efficiency water reducer.

[0052] Among them, slag powder is granulated blast furnace slag powder, which is a commonly used concrete admixture. The slag powder added in this comparative example is ground and has a specific surface area of ​​400m 2 / kg or more.

[0053] Other raw materials and preparation methods are the same as those in Example 1.

[0054] Comparative Example 3 A graphene oxide-modified UHPC is prepared from raw materials comprising the following components in parts by mass: 1467 parts of 52.5-grade ordinary Portland cement, 147 parts of incompletely densified silica fume, 85 parts of steel slag, 0.44 parts of graphene oxide, 39 parts of copper-plated straight steel fibers, 452 parts of tap water, and 6 parts of a polycarboxylic acid-based high-efficiency water reducer.

[0055] The steel slag is converter steel slag, which has a specific surface area of ​​400m after grinding. 2 / kg or more.

[0056] Performance Testing Conventional mechanical tests and high-speed projectile penetration resistance tests were performed on Examples 1 to 4 and Comparative Example 1, wherein the conventional mechanical tests included compressive strength, elastic modulus, and flexural strength; the high-speed projectile penetration resistance test process was the same as that of the Chinese patent application "Anti-penetration ultra-high performance concrete, preparation method, and application" with application number 2023117815297, but the target speed was increased from 400 m / s to 650 m / s, and the penetration depth, crater diameter, and projectile mass loss rate were collected. The performance test results are shown in Table 1.

[0057] Table 1 Performance test results

[0058] By comparing Table 1, it can be found that the compressive strength, elastic modulus and flexural strength of the examples are improved to varying degrees compared with those of comparative example 1. With the increase of the content of graphene oxide, the static mechanical properties are enhanced accordingly. However, after reaching a certain threshold, further increasing the content of graphene oxide has little effect on the performance improvement of ultra-high performance concrete. It can be seen that the significant improvement in compressive strength is mainly attributed to: the nanoscale of graphene oxide enables it to effectively fill the micropores in the cement matrix, significantly improve the density of concrete, and reduce the porosity; at the same time, graphene oxide has an extremely high specific surface area, and its surface contains oxygen-containing functional groups such as carboxyl, hydroxyl and epoxy groups, such as Figure 1 As shown, these functional groups can bind to calcium ions (Ca² + ) produces complexation, promoting the formation of CSH gel and the growth of hydrated crystals, forming a denser microstructure.

[0059] The significant improvement in elastic modulus is mainly attributed to the fact that the oxygen-containing functional groups of graphene oxide can form complexes with calcium ions in the cement matrix, significantly enhancing the interfacial strength between the cement matrix and aggregate. The ITZ is the most vulnerable area in concrete, and graphene oxide plays a reinforcing role in this area, thereby increasing the elastic modulus of the material. At the same time, graphene oxide promotes the formation of CSH gel, which is the main bonding material in the cement hydration process and can significantly enhance the mechanical properties of concrete. Through the catalytic effect of graphene oxide, more CSH gel is generated, further improving the rigidity of the material.

[0060] The significant improvement in flexural strength is mainly attributed to the fact that the two-dimensional nanosheet structure of graphene oxide acts as a bridge during the propagation of microcracks, preventing the cracks from further expanding, thereby improving the flexural strength of the material. This effect is particularly important for preventing fractures caused by bending. As a reinforcing material, graphene oxide interweaves with the hydration products in the cement matrix to form a tight network structure, which improves the ductility and toughness of concrete under stress and reduces the occurrence of cracks.

[0061] The significant improvement in the penetration resistance of ultra-high performance concrete is mainly attributed to: 1) Graphene oxide greatly improves the impact and penetration resistance of concrete. Graphene oxide effectively resists the intrusion of external impact loads by improving the pore structure and enhancing the density of the microstructure, reducing the penetration depth and significantly improving the performance of concrete under impact loads. 2) The reduction in the pit diameter shows the effectiveness of graphene oxide in resisting impact damage. Graphene oxide can reduce surface damage caused by impact through filling and reinforcement effects. The expansion of cracks caused by impact loads is organized through bridging action, reducing the surface damage area. At the same time, the dense and uniform distribution of the material improves the toughness of the material and reduces the material damage caused by stress concentration.

[0062] The graphene oxide dosage (mass percentage) in Examples 1 to 4 and Comparative Example 1 was calculated to obtain the relationship between the graphene oxide dosage and the penetration depth and the pit diameter, as shown in FIG. Figure 4 As shown: the performance is best when the graphene oxide dosage is 0.03-0.04%, corresponding to Example 2 and Example 3.

[0063] Although steel slag and slag powder are common additives in concrete, their raw materials are subjected to high temperatures during processing, so the particle surface is relatively smooth and the bond between them and the matrix is ​​relatively sparse, unable to form a dense rigid whole. Therefore, the improvement in anti-penetration performance is not significant, and the effect corresponds to proportions 2 and 3.

[0064] Therefore, the present invention provides an ultra-high performance concrete with excellent resistance to high-speed projectile penetration and mechanical properties, and its anti-penetration performance is significantly higher than that of the ultra-high performance concrete without graphene oxide modifier in comparative example 1. It can be seen that the CSH gel and hydrate crystals formed by the addition of graphene oxide modifier are beneficial to improving the anti-penetration performance of ultra-high performance concrete; on the one hand, the graphene oxide modifier can promote the generation of CSH gel and hydrate crystals in ultra-high performance concrete, forming a denser microstructure and improving the mechanical properties of the material; on the other hand, the graphene oxide modifier can provide more landing points to facilitate the generation and expansion of hydrate crystals, repair the pores and cracks in the transition zone between the matrix and the interface, and greatly improve the anti-penetration performance of the material. The optimization of the anti-penetration performance and mechanical properties of ultra-high performance concrete by the graphene oxide modifier enables it to be used as a modern new protective material.

[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A UHPC based on graphene oxide modification, characterized in that: The invention is prepared from raw materials including the following components in parts by weight: 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 0.29-0.73 parts of graphene oxide, 410-510 parts of water and 6-12 parts of water reducing agent; wherein the molecular structure of graphene oxide is: .

2. The UHPC based on graphene oxide modification according to claim 1, characterized in that: The cement is ordinary Portland cement of grade 52.5 or grade 52.5R.

3. The UHPC based on graphene oxide modification according to claim 1, characterized in that: The silica ash has an amorphous silicon dioxide content greater than 95wt% and a specific surface area greater than 21.0 m 2 / g.

4. The UHPC based on graphene oxide modification according to claim 1, characterized in that: The steel fiber is ordinary Mercedes-Benz steel fiber or copper-plated straight steel fiber.

5. The UHPC based on graphene oxide modification according to claim 1, characterized in that, The water reducing agent is a polycarboxylic acid water reducing agent.

6. A method for preparing UHPC based on graphene oxide modification according to any one of claims 1 to 5, characterized in that: include: S1, mixing graphene oxide and water to obtain a graphene oxide dispersion; S2, cement and silica fume are mixed to obtain a first mixture; S3, adding the graphene oxide dispersion to the first mixture, and mixing to obtain a second mixture; S4. Add steel fiber to the second mixture, mix and stir to obtain the graphene oxide-modified UHPC.

7. The method for preparing UHPC based on graphene oxide modification according to claim 6, characterized in that: In S1, the mixing method is ultrasonic stirring for 1 to 2 hours; in S2, the mixing method is stirring at a speed of 75-85 rpm for 2 to 3 minutes; in S3, the mixing method is stirring at a speed of 75-85 rpm for 2 to 3 minutes; in S4, the mixing and stirring method is stirring at a speed of 155-165 rpm for 3 to 5 minutes.

8. The method for preparing UHPC based on graphene oxide modification according to claim 6, characterized in that: The method comprises step S5, mixing the graphene oxide-modified UHPC, casting it into a mold and curing it to a specified age.

9. The method for preparing UHPC based on graphene oxide modification according to claim 8, characterized in that: In S5, the stirring method is stirring at a rotation speed of 355-365 rpm for 3-5 minutes; In S5, the curing method is curing under standard curing conditions.

10. An application of UHPC modified with graphene oxide as claimed in any one of claims 1 to 5, characterized in that: Including applications in military protection engineering or civil structural engineering.

Citation Information

Patent Citations

  • Concrete with high tensile strength and ultra-high performance and preparation method thereof

    CN117326834A